Predictive Factors of Outcome in Cases of Out-of-hospital Cardiac Arrest Due to Traffic Accident Injuries in Thailand; a National Database Study - Huabbangyang, Thongpitak; Sangketchon, Chunlanee; Ittiphisit, Sakditat; Uoun, Kanittha; Saumok, Chomkamol (Archives of Academic Emergency Medicine, 2022)
Introduction: Traffic accident injury is one of the global leading causes of death and an important public health problem. This study aimed to evaluate the predictive factors of return of spontaneous circulation (ROSC) at the scene in out-of-hospital cardiac arrest (OHCA) due to traffic accidents. Methods : This retrospective cross-sectional study was conducted on cases of OHCA due to traffic accident, who were resuscitated at the scene by emergency medical services (EMS) in Bankok, Thiland, from January 1, 2020, to December 31, 2020 (1 year). Patients were divided into two groups of with and without ROSC and independent predictive factors of outcome were evaluated. Results : 2400 OHCA cases met the inclusion criteria, among them, 1728 (72.0%) achieved ROSC at the scene. Facial injury (adjusted OR = 2.17, 95%CI: 1.37–3.44, p = 0.001); prehospital airway management using bag valve mask (adjusted OR = 1.69, 95%CI: 1.21–2.34, p = 0.002), and endotracheal tube (adjusted OR = 3.88, 95%CI: 1.84–8.18, p <0.001); and prehospital fluid therapy using normal saline (adjusted OR = 4.24, 95%CI: 3.12–5.77, p <0.001), ringer lactate (adjusted OR = 5.13, 95%CI: 3.47–7.61, p <0.001), and other solutions (adjusted OR = 5.25, 95%CI: 2.16–12.8, p <0.001) were independent predictive factors of ROSC at the scene in OHCA due to traffic accidents. Conclusion : Based on the findings, the rate of ROSC at the scene for cases with OHCA due to traffic accidents, serviced by EMS was high, i.e., 72%, and three independent predictive factors of ROSC at the scene were facial injury, prehospital airway management, and prehospital fluid management.